Comparative Plasmodium gene overexpression reveals distinct perturbation of sporozoite transmission by profilin - Sato, Yuko (The American Society for Cell Biology, 2016)
The roles of vital genes, such as those of G-actin–binding proteins, in malaria parasites are underexplored. Overexpression of Plasmodium profilin perturbs actin dynamics only in sporozoites. Strict actin regulation is particularly important for malaria transmission. Mapping of phenotypes can be done by comparative Plasmodium gene overexpression.